Peranan Komunikasi Politik Partai dalam Meningkatkan Pendidikan Politik bagi Masyarakat Kabupaten Sikka - Higinus Wilbrot; Yusuf Yusuf (Jurnal Ilmu Sosial dan Humaniora, 2026)
Political education is a crucial instrument for fostering political awareness and participation among citizens who are critical and rational. In Sikka Regency, East Nusa Tenggara, political parties play a strategic role as primary agents in conducting political communication and education. This study aims to: (1) Analyze the forms and channels of political communication used by political parties in Sikka Regency; (2) Assess the effectiveness of party political communication in enhancing public political education; and (3) Identify the structural and cultural obstacles encountered in this political communication process. The study employs a descriptive qualitative approach. Primary data were obtained through in-depth interviews with political party officials (at the branch and regional levels in Sikka), community leaders, local academics, and the general public in both urban areas (Maumere) and island or remote inland areas. Secondary data were gathered from documents provided by the General Elections Commission (KPU) and the Sikka Regency National Unity and Politics Agency (Kesbangpol), as well as from social media sources. The findings indicate that political communication conducted by parties in Sikka Regency utilizes two main approaches: formal communication (legislative recess periods, branch conferences, and program dissemination) and cultural communication rooted in local wisdom (such as *Kula Babong* or traditional deliberation practices). Digital media, including Facebook and WhatsApp groups, are also being extensively used to reach young voters. However, the effectiveness of this political communication in delivering substantive political education remains moderate. This is attributed to the prevalence of communication that is seasonal in nature—occurring primarily in the lead-up to general or regional elections—and the persistence of a pragmatic political culture (characterized by "money politics"). The study concludes that political communication based on local wisdom needs to be institutionalized on a sustainable basis—beyond election periods—to foster transformative political education in Sikka Regency.